2014
DOI: 10.3390/metabo4010131
|View full text |Cite
|
Sign up to set email alerts
|

Applications of NMR in Dairy Research

Abstract: NMR is a robust analytical technique that has been employed to investigate the properties of many substances of agricultural relevance. NMR was first used to investigate the properties of milk in the 1950s and has since been employed in a wide range of studies; including properties analysis of specific milk proteins to metabolomics techniques used to monitor the health of dairy cows. In this brief review, we highlight the different uses of NMR in the dairy industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 55 publications
0
19
1
Order By: Relevance
“…with two other recent studies, where no relationship was found between blood and milk 542 metabolic profiles (Zhang et al, 2013;Maher and Rochfort, 2014). The blood metabolite 543 profile does not appear to be either a reliable indicator of energy balance and concurrent milk 544 production or a predictor of future changes in these parameters.…”
Section: Change 533contrasting
confidence: 49%
“…with two other recent studies, where no relationship was found between blood and milk 542 metabolic profiles (Zhang et al, 2013;Maher and Rochfort, 2014). The blood metabolite 543 profile does not appear to be either a reliable indicator of energy balance and concurrent milk 544 production or a predictor of future changes in these parameters.…”
Section: Change 533contrasting
confidence: 49%
“…Differences in the detected compounds may be due to the difference in the animals' health status, in the animals' diet and management, and in animal genetics among studies. The 1 H-NMR technique represents one of the most sensitive techniques that allows detection of metabolites in bio-fluids with high sensitivity, and it is quantitative, highly reproducible, and straightforward to use [29,30]. The present study investigated if the parity of the sow can influence the metabolomics profile of swine defatted colostrum and explain differences in the productive performance.…”
Section: Discussionmentioning
confidence: 99%
“…NMR has the ability to serve as an invaluable tool for the compositional analysis of foods, not only due to its ability to provide important information for structural elucidation, but also for its quantitative nature. NMR has been effectively used for the analysis of several classes of compounds including lipids (Dais & Hatzakis, ; Monakhova & Diehl, , ; Siddiqui et al., ; Tsiafoulis et al., ), carbohydrates (Kazalaki et al., ; Merkx, Hong, Ermacora, & van, ; Singh, Kumar, Srivastava, Deepak, & Singh, ; Spraul et al., , ), amino acids (Belton et al., ), alcohols (Hatzakis, Archavlis, & Dais, ; Nilsson et al., ), organic acids (Berregi, del Campo, Caracena, & Miranda, ), polyphenols (Agiomyrgianaki & Dais, , ; Charisiadis, Exarchou, Troganis, & Gerothanassis, ), vitamins (Ackermann et al., ; Dais et al., ; Shumilina, Ciampa, Capozzi, Rustad, & Dikiy, ; Vaysse et al., ), terpenes (Dais, Plessel, Williamson, & Hatzakis, ), phospholipids (Hatzakis, Koidis, Boskou, & Dais, ; Kaffarnik, Ehlers, Gröbner, Schleucher, & Vetter, ), colorants (Englert, ; Scotter, ; Venkatachalam et al., ; Berké, Chèze, Vercauteren, & Deffieux, ), and contaminants (Lachenmeier et al., ) in a variety of foods, such as oils (Dais & Hatzakis, ; Siddiqui et al., ), beverages (Kidrič, ; Ryu, Koda, Miyaka, & Tanokura, ; Santos, Fonseca, Lião, Alcantara, & Barison, ; Zurriarrain et al., 2015), meats (García‐García et al., ), dairy products (Gangwar, Singh, & Deepak, ; Hu, Furihata, Ito‐Ishida, Kaminogawa, & Tanokura, ; Maher & Rochfort, ; Murgia, Mele, & Monduzzi, ; Scano et al., ; Tociu et al., ), and infant formula (Zhao et al., ). For the structural characterization of various food components, the application of 2D techniques is often required.…”
Section: Fundamentals Of Nmr Spectroscopy‐relevance To Food Sciencementioning
confidence: 99%
“…NMR spectroscopy has been used for the quality control of foods in terms of monitoring stability (Alonso‐Salces, Holland, & Guillou, ; Guillen & Goicoechea, ; Lamanna, Piscioneri, Romanelli, & Sharma, ; Souza, Martínez, Ferreira, & Kaiser, ), storage history (Belloque et al., ; Fronimaki et al., ; Graham et al., ), packaging (Pentimalli et al., ), safety (Beer et al., ; Marchand et al., ; Monakhova, Kuballa, & Lachenmeier, ), evaluation of agronomic practices (Consonni et al., ; Gallo et al., ; Jahangir et al., ; Winning et al., ; Zhang, Breksa, Mishchuk, & Slupsky, ), and studying process‐induced effects (Alves Filho et al., ; García‐García, Lamichhane, Castejón, Cambero, & Bertram, ; Lopez‐Sanchez et al., ; Sinanoglou et al., ; Vermathen et al., ; Wakamatsu, Handa, & Chiba, ; Zoumpoulakis et al., ; Hwang et al, ). Characteristic examples of foods include fish (Erikson et al., ; Martinez et al., ; Tan et al, ), meat (Straadt, Aaslyng, & Bertram, ), spices (Cagliani, Culeddu, Chessa, & Consonni, ; Ordoudi et al., ), beverages (Almeida et al., ; Le Gall, Colquhoun, & Defernez, ; Spevacek, Benson, Bamforth, & Slupsky, ; Walch, Stühlinger, Lachenmeier, Monakhova, & Kuballa, 2012a), oils (Lucas‐Torres, Pérez, Cabañas, & Moreno, ), and dairy products (Maher & Rochfort, ; Shintu & Caldarelli, ). Recently, NMR, combined with statistical analysis, was used to determine the quality of salmon relating to its storage conditions (Shumilina, Dykyy, & Dikiy, ).…”
Section: Fundamentals Of Nmr Spectroscopy‐relevance To Food Sciencementioning
confidence: 99%